METODE PENGEMBANGAN DIRI USTAZ DAYAH TERPADU (SUATU TINJAUAN PSIKOLOGI ISLAM) - Nurbayani Nurbayani (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
The method of developing self-image in the context of psychological education is character building based on the concept of Islamic education based on unity and discipline. Integrated Dayah Integrated Law in an effort to develop its image emphasizes the integration of values, namely knowledge transformation, skills development, and value planting. The research instrument used was an open interview aimed at obtaining multiple perspectives on motivation to participate in religious activities. This is based on efforts to improve the quality of religious teachers as a top priority. The results showed that the imagery of the Integrated Dayah Ustad can be realized in the life of the dayah because it is influenced by the internal and external factors of the family, namely the influence outside the home or social institutions that support the community. However, the existence of dayah leaders who remain in their hearts, namely educating and passing on their knowledge and modeling them to other religious teachers, will show that the image of the Integrated Dayah ustaz still exists in contemporary society.